2018
DOI: 10.1016/j.ijsu.2017.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive versus extensile lateral approach for sanders type II and III calcaneal fractures: A meta-analysis of randomized controlled trials

Abstract: Our meta-analysis suggests that MI and ELA are equally effective treating Sanders type II and III fractures. However, MI is effective in improving the AOFAS score (Sanders type II); reducing the rate of wound complications; and shortening the time to surgery, duration of surgery and length of hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 28 publications
4
40
0
Order By: Relevance
“…Additionally, the total number of patients included in their meta-analysis was only 532 [ 19 ]. Zeng et al similarly completed a meta-analysis of minimally invasive versus extensile lateral approaches for Sanders type 2 and 3 calcaneal fractures but were only able to include 495 participants from eight randomised trials [ 20 ]. Lastly, Yao et al report a meta-analysis of 1078 participants on the topic and claim to have identified improved wound healing and functional outcomes associated with a sinus tarsi approach.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the total number of patients included in their meta-analysis was only 532 [ 19 ]. Zeng et al similarly completed a meta-analysis of minimally invasive versus extensile lateral approaches for Sanders type 2 and 3 calcaneal fractures but were only able to include 495 participants from eight randomised trials [ 20 ]. Lastly, Yao et al report a meta-analysis of 1078 participants on the topic and claim to have identified improved wound healing and functional outcomes associated with a sinus tarsi approach.…”
Section: Discussionmentioning
confidence: 99%
“…The new operation method was simple and the surgery process was smooth, and a good postoperative effect was achieved. Moreover, the surgery time was just 28.16 ± 10.70 min as compared to > 60 min for classic calcaneal fracture MIIF and ORIF [17,29]. The operation was guided at each step by the PSI, which facilitated the surgical procedure and eliminated the need for extensive intraoperative fluoroscopy, resulting in near-perfect fracture reduction and internal fixation.…”
Section: Discussionmentioning
confidence: 99%
“…d Two posterior cannulated screws were inserted to fix the main body of the calcaneus axially 3-8 weeks, followed by partial weight bearing for several weeks according to the doctor's advice. Full weight bearing was allowed when radiographs showed evidence of osseous union, generally at 3 months post surgery [17,18].…”
Section: Postoperative Managementmentioning
confidence: 99%
“…The new operation method was simple and the surgery process was smooth, and a good postoperative effect was achieved. Moreover, the surgery time was just 28.16±10.70 min as compared to >60 min for classic calcaneal fracture MIIF and ORIF [17,29]. The operation was guided at each step by the PSI, which facilitated the surgical procedure and eliminated the need for extensive intraoperative uoroscopy, resulting in near-perfect fracture reduction and internal xation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were encouraged to engage in non-weightbearing mobilization for the rst 3-8 weeks, followed by partial weight bearing for several weeks according to the doctor's advice. Full weight bearing was allowed when radiographs showed evidence of osseous union, generally at 3 months post surgery [17,18].…”
Section: Postoperative Managementmentioning
confidence: 99%